Profile of School Well-Being of Women's Students Based on the Dimensions of Having, Loving, Being, and Health - Indra Wijaya; Andi Tajuddin; Sry Hasriny (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study aims to describe the profile of school well-being female students based on four main dimensions according to Konu and Rimpela, namely having, loving, being, and health. The study used a descriptive quantitative approach involving 172 female students from five Islamic boarding schools in South Sulawesi who were selected through purposive sampling techniques. The instrument used was the School Well-Being Scale adapted from the Konu and Ripela models, consisting of 41 valid items with a reliability of α = 0.857. The results showed that the overall level of school well-being of female students was in the medium category (M = 2.75), with 70.35% of respondents in the medium category, 14.53% in the high category, and 15.12% in the low category. The loving (M = 3.27) and being (M = 3.10) dimensions had the highest values, while having (M = 2.29) and health (M = 2.34) showed lower values. This pattern is consistent across all five pesantren, indicating that dimensional inequality is a structural issue. These findings have practical implications for pesantren managers in designing more targeted dimension-based interventions